Hydrocephalus in Neurofibromatosis Type 1 Caused by a Cyst Formation Similar to Late-Onset Aqueductal Membranous Occlusion: A Case Report and Review of Literature - Kuwahara, Kiyonori; Ohba, Shigeo; Ganaha, Tsukasa; Murayama, Kazuhiro; Abe, Masato; Hasegawa, Mitsuhiro; Hirose, Yuichi (Asian Journal of Neurosurgery, 2022)
Cyst formation in the third ventricle and the histopathological findings were rarely reported. We report a similar case of late-onset aqueductal membranous occlusion (LAMO) caused by a thin gliotic cyst and a review of related literature. A 28-year-old woman with enlarged lateral ventricles was referred to our hospital with complaints of headache and dizziness. In our hospital, the obvious cause of the hydrocephalus was unknown on any examination and we decided performing endoscopic third ventriculostomy for hydrocephalus. A thin cyst covering the entrance of the aqueduct was identified and we perforated it. Histopathological finding of the cyst wall was gliosis and our case was similar to LAMO, although not typical. The postoperative symptoms and ventricle size improved for 4 years. When suspecting cases similar to definition of LAMO, neuroendoscopic surgery would be the first-choice treatment and might detect causes undetectable on preoperative imaging such as our thin membrane.
Keywords: hydrocephalus; late-onset aqueductal membranous occlusion; time-SLIP